IDENTIFIKASI LOKASI GANGGUAN BERBASIS PMU PADA SISTEM 20 KV BAWAH LAUT PULAU PISANG - Eddy Prayitno; Khairudin; Misfa Susanto (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Fault location identification in power systems is crucial for maintaining reliability, especially in Medium Voltage Submarine Cable Systems. This study discusses PMU-based fault location identification in a 20 kV subsea system at Pulau Pisang. Two methods are applied: impedance-based method and Traveling Wave method. Simulations are conducted using MATLAB/Simulink to analyze waveform behavior before and after faults. Results show significant voltage drops, current surges, and phase instability during faults. The Traveling Wave method provides faster and more accurate fault detection. This study demonstrates that PMU implementation enhances the speed and accuracy of fault location identification in subsea power systems. Faults in the 20 kV subsea system can cause a loss of power supply to Pulau Pisang. Therefore, it is important to be able to identify the fault location quickly and accurately so that it can be repaired immediately. Pulau Pisang is a strategic location that requires a reliable electrical infrastructure, especially since it is located under the sea. Fault location identification based on PMU in the 20 kV system aims to improve efficiency, accuracy, and reliability in detecting and isolating faults that occur in the electrical network.